Identity of Kurdishness of Fahlavi's poetry - Mohammed, Rizgar Tayeb (Sulaimani Journal for Humanities, 2025)
The history of Kurds and Kurdistan, like the history of all nations, is full of ups and downs. However, the history of Kurds and Kurdistan is full of gaps, separations and dark corners, some of which are lost and unwritten history, some of which are false and distorted history, and some of which are stolen history. Part of the history and culture of nations has been more or less rewritten by others, especially neighboring and dominant nations. This is not without emotional and hostile views. This is even more confusing for the Kurdish nation. Especially the period after the Muslim Arab globalization invasions until the beginning of the emergence of the scientific method of writing history in all its dimensions. For so long, the Kurds themselves have made little effort to record their history and culture. Much of its history has been rewritten by nations that have had cultural and political domination over the Kurds and their country. They are the Arab, Persian and Turkish nations. Even all the scientific theses and theories put forward by orientalists have been used by the invaders of Kurdistan to impose their ownership of the ancient wisdom and culture that existed in this country. One of the cultural heritage of the past is Fahlavi poetry and literature, the noble example of which is the poems of Baba Tahir Hamadan (10th and 11th centuries AD). Although Kurds consider Baba Tahir to be the pioneer of the history of Kurdish literature, there is still no clear picture of the linguistic identity of Baba Tahir and other poets of that literature. In this research, an attempt has been made to highlight the Kurdish identity of the language of this literature through descriptive methods and historical analysis and to prove that the heir of this literature is Kurdish. In addition to introducing a number of Fahlavi poets like Baba Tahir.
Keywords: Fahlavi poetry; Kurdish language; Kurdish identity